Impact of cross-border telework taxation in the EU. Are new criteria for the allocation of income between States necessary? - Ferrer Vidal, Diana (CUADERNOS DE DERECHO TRANSNACIONAL, 2026)
Remote work in the European Union, driven by digitalization and the pandemic, poses unprecedented tax challenges. Virtual mobility blurs traditional taxation boundaries, creating uncertainty about which State is competent to levy income. The figure of the cross-border teleworker and the digital nomad intensifies competition among Member States to attract tax residents, questioning classical principles of territoriality and residence. This study examines the regulatory framework aplicable when the worker operates from a country different from that of the employer. Should taxation occur in the State of work or in the State of the company’s headquarters? Based on the proposals of the European Economic and Social Committee and Social Security regulations, criteria are suggested to harmonize telework taxation, ensuring legal certainty and administrative simplification.